A Poly(dimethyl-co-methylvinyl)siloxane-based elastomer with excellent ultra-low temperature elasticity driven by flexible alkyl branches. (5th July 2022) - Niu, Zhen; Wu, Ruiyao; Huang, Lingyun; Yang, Yinxin; Xia, Zhu; Fan, Weifeng; Sun, Wu; Dai, Quanquan; He, Jianyun; Bai, Chenxi
Graphical abstract: Highlights: The poly(dimethyl-co-methylvinyl)siloxane-based elastomer with a glass transition temperature ( Tg ) lower than −120 °C. The elastomer exhibits long-time (exceed 3000 s) excellent elasticity at −110 °C. The average cross-linking density of elastomers is 6 times than its counterpart polydimethylsiloxane. The facile polymerization and efficient thiol-ene addition post-polymerization enables the large-scale preparation of the ultra-low temperature elastomer. Abstract: Elastomers that services under ultra-low temperature environments are of great strategic and technological importance. Among them, polysiloxanes are excellent precursors, however, the unfavorable crystallization greatly limits its ultra-low temperature application. Herein, we explore the synthesis, glass transition temperature ( Tg ), cross-linking behavior and long-time ultra-low temperature elasticity characterization of polydimethylsiloxane (PDMS) with flexible alkyl branches. The results demonstrated that the flexible alkyl branches play a dual role in PDMS, for it can not only unlock its ultra-low temperature elasticity by suppressing crystallization, but also provide more free radical attack sites to enhance the cross-linking activity. The resulting elastomer with a Tg lower than −120 °C exhibits excellent elasticity at such a low temperature down to −110 °C. Moreover, the facile and efficient one-step thiol-ene addition post-polymerization enables the large-scale preparation of this ultra-low temperature elastomer. The work demonstrated here reveals a general practical strategy to unlock PDMS ultra-low temperature performance, which is conducive to the development of cutting-edge scientific research.